LEXICAL BORROWING OF SOCIAL MEDIA TERMS IN LIPUTAN6.COM WEBSITE - Lista Indriani; Barli Bram (JOURNAL OF LANGUAGE, 2023)
This article explored the application of borrowed English words, mainly social media terms, on the website Liputan6.con. The urgency of this study is to highlight the development of the Indonesian language, which has experienced integration with foreign languages over time and one factor is the progress of technology in which there is no limit or restriction in spreading information. This study focused on identifying the types of borrowed words used in Liputan6.com. The researchers employed a variety of theories and borrowed words. This study used content analysis as a research method to explore the types of 50 borrowed words found on the website. Reading through the actual website posts, categorizing the borrowed words, and analyzing the collected data were carried out in the data analysis. The authors discovered three different types of borrowing words in the social media section of Liputan6.com. They were Loan Blends, used 33 times; Loan Shifts, appearing 36 times; and Loan Words, used 17 times.